(untitled) (Revista Científica Compendium, 2019)
Within the institutional context, business foundations represent organizational forms that usually have an impact on the expectations, perceptions and evaluations that the stakeholders carry out of the business behavior, derived from their particular nature and the relative or conjuncture influence on the development of core activities carried out by the parent company. For this reason, this essay addresses the conceptual considerations that facilitate the strategic understanding of the contribution that business foundations generate in the processes of organizational legitimacy and sustainability. Among the revealed aspects, it is presupposed those represent a collateral bridge as a way of demonstrating the policies, strategies and management methods to achieve and reinforce the legitimacy of the companies on which they generally depend, or are closely linked.